ANALISIS KESESUAIAN PENERAPAN BIOSECURITY PADA PETERNAKAN AYAM BROILER SISTEM CLOSED HOUSE DAN OPEN HOUSE BERDASARKAN PERATURAN PERUNDANG-UNDANGAN (Studi Kasus Desa Abbumpungeng Kecamatan Cina Kabupaten Bone) - Fitriani Fitriani; Irmayani Irmayani; Nur Hapsa; Nurul Amin (Jurusan Peternakan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2026)
This study aims to analyze the level of compliance in the implementation of biosecurity based on legislative regulations in broiler chicken farms using closed house and open house systems in Abbumbungeng Village, Cina District, Bone Regency. The research was conducted through observation, interviews, and documentation. The variables observed included closed house housing, open house housing, external biosecurity, and internal biosecurity.The results showed that the implementation of external biosecurity in the closed house system was categorized as very good, with a percentage of 89.0%, and internal biosecurity also reached 89.0%. Meanwhile, in the open house system, the implementation of external biosecurity was 40.1% and internal biosecurity was 60.0%. Based on the overall results, the implementation of biosecurity in the closed house system is better than in the open house system. However, both systems still require improvements in the implementation of biosecurity, both external and internal. Keywords: Closed House, Open House, Internal Biosecurity, External Biosecurity